Determination of Paraquat Using Microfluidic Paper-Based Analytical Device (µPAD) Immobilized with p-Hydroxybenzoic Acid Capped Silver Nanoparticles - Gusrizal, Gusrizal; Budi, Firman Shantya; Puspita, Dewi (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2026)
This study developed a microfluidic paper-based analytical device (µPAD) immobilized with p-hydroxybenzoic acid capped silver nanoparticles (AgNPs-PHB) for the colorimetric detection of paraquat (PQ) in water samples. The synthesized AgNPs-PHB exhibited favorable properties, including a nanoscale size (68.5 nm by DLS, 20 nm by TEM), high stability (zeta potential of -53 mV), and a spherical morphology, as confirmed by UV-Vis spectroscopy, PSA, and TEM analysis. The µPAD platform utilized a wax-printed hydrophobic barrier to direct sample flow, enabling a simple and cost-effective detection method. Upon interaction with PQ, AgNPs-PHB underwent aggregation, resulting in a visible color change from yellow to gray, which was quantified using ImageJ software for RGB analysis. The method demonstrated excellent linearity (R2 = 0.9917 for red intensity) across a concentration range of 0.001 - 0.01 M, with a limit of detection (LOD) of 0.00060 M and a limit of quantification (LOQ) of 0.0020 M. Precision tests revealed high repeatability and reproducibility, with intraday and interday %RSD values below 2%. Recovery studies in tap water, drainage water, and well water samples spiked with PQ yielded accurate results (99.7–102.5%), validating the method’s reliability. Compared to conventional techniques, this µPAD-based approach offers a portable, environmentally friendly, and sensitive alternative for monitoring PQ contamination in environmental water samples, making it suitable for field applications.